Comparing Diet Quality of Racial Minority Children from Low-Income Households During the Summer versus School Year: Results from the Project SWEAT Study (P04-102-19) - Hopkins, Laura (Curr Dev Nutr, 2019)
OBJECTIVES: Compare the diet quality of racial minority school-age children from low-income households during the summer versus school year. METHODS: Two elementary schools in low-income urban neighborhoods of Columbus, OH were recruited. Families with children at these schools were invited to participate. Caregivers completed a demographic survey at baseline (t0). Child diet was assessed using three 24-hr dietary recalls (2 weekdays and 1 weekend day) at 3 time points: 1) baseline/beginning of summer (t0); 2) middle of summer (t1); and 3) beginning of subsequent school year (t2). Demographic data were summarized. Healthy Eating Index (HEI) 2015 was calculated: total [100] and component [Adequacy: total fruit (5), whole fruit (5), total vegetable (5), greens and beans (5), whole grains (10), dairy (10), total protein (5), seafood and plant protein (5), fatty acids (10); Moderation: refined grains (10), sodium (10), added sugars (10), saturated fats (10)]. Paired t-tests were conducted to determine differences in diet quality between time points (t0: t1, t1: t2, t0: t2). RESULTS: 62 children (39 families) enrolled. Mean age was 7.08 ±0.34 yr, 80.67% were African American, and 69.35% low-income. Participant retention from t0: t1 and t0: t2 was 95.16% and 75.81%. Mean total HEI was 47.37 ± 1.57 (t0), 47.51 ± 1.22 (t1), and 51.13 ± 1.46 (t2) with significant differences between summer and school year time points (t0: t2, P = 0.02; t1: t2, P = 0.01). Significant differences in adequacy and moderation HEI component scores between the two summer time points and school year time point were observed such that child diet quality was better during the school year. Adequacy: whole fruit (t1: t2 P = 0.02), total vegetable (t0: t2 P < 0.01; t1: t2 P < 0.01), greens beans (t0: t1 P < 0.01; t1: t2 P < 0.01), and seafood and plant protein (t0: t2 P = 0.06; t1: t2 P = 0.08). Moderation: sodium (t0: t2 P = 0.07) and added sugar (t0: t2 P = 0.06; t1: t2 P = 0.02). The HEI component score for whole grains was significantly better during the summer compared to the school year (t0: t2 P < 0.01; t1: t2 P < 0.01). CONCLUSIONS: Except for whole grains, child diet quality is better during the school year versus summer. Findings from this study provide the first insight into potential determinants of unhealthy weight gain observed among economically disadvantaged, school-age children during the summer months. FUNDING SOURCES: USDA North Central Nutrition Education for Excellence.